MILAN MACHOVEC – MARKSISTOWSKI „PROROK” HUMANISTYCZNEGO DIALOGU? - Puzia, Robert (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article presents the problem of understanding of the concept of the Marxist – Christian dialogue in the thought of the Czech Marxist philosopher Milan Machovec. The author of the article poses the question about the possibility of such dialogue and by taking notice to the tree aspects, he tries to give the answer to this question. The article presents first the most important stages in the biography of Machovec, then analyzes understanding of the issue of God and of the issue of dialogue in the thought of the Czech philosopher. This made it possible to outline the context, in which it is possible to answer the question about the possibility of the Marxist – Christian dialogue.